2021
DOI: 10.1111/tpj.15259
|View full text |Cite
|
Sign up to set email alerts
|

The flexibility of metabolic interactions between chloroplasts and mitochondria in Nicotiana tabacum leaf

Abstract: To examine the effect of mitochondrial function on photosynthesis, wild-type and transgenic Nicotiana tabacum with varying amounts of alternative oxidase (AOX) were treated with different respiratory inhibitors. Initially, each inhibitor increased the reduction state of the chloroplast electron transport chain, most severely in AOX knockdowns and least severely in AOX overexpressors. This indicated that the mitochondrion was a necessary sink for photo-generated reductant, contributing to the 'P700 oxidation ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 123 publications
(171 reference statements)
0
19
0
Order By: Relevance
“…A key role of respiratory flexibility as mediated by UCP1 has been attributed to photorespiratory metabolism, but also drought and salt stress responses ( Sweetlove et al, 2006 ; Begcy et al, 2011 ; recently reviewed by Barreto et al, 2020 ). Loss of AOX1a has been reported to increase susceptibility of leaves to combined drought and light stress and other conditions challenging the energy and/or carbon balance in the photosynthetic cell, in agreement with a role in providing an electron sink to avoid photoinhibition ( Giraud et al, 2008 ; Smith et al, 2009 ; Kühn et al, 2015 ; Shapiguzov et al, 2019 ; Alber and Vanlerberghe, 2021 ) . AOX1a has been extensively studied as a core stress response gene in Arabidopsis, emphasizing the general need for avoiding metabolic over-reduction under a variety of stress conditions ( Escobar et al, 2006 ; Giraud et al, 2008 ; Smith et al, 2009 ).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…A key role of respiratory flexibility as mediated by UCP1 has been attributed to photorespiratory metabolism, but also drought and salt stress responses ( Sweetlove et al, 2006 ; Begcy et al, 2011 ; recently reviewed by Barreto et al, 2020 ). Loss of AOX1a has been reported to increase susceptibility of leaves to combined drought and light stress and other conditions challenging the energy and/or carbon balance in the photosynthetic cell, in agreement with a role in providing an electron sink to avoid photoinhibition ( Giraud et al, 2008 ; Smith et al, 2009 ; Kühn et al, 2015 ; Shapiguzov et al, 2019 ; Alber and Vanlerberghe, 2021 ) . AOX1a has been extensively studied as a core stress response gene in Arabidopsis, emphasizing the general need for avoiding metabolic over-reduction under a variety of stress conditions ( Escobar et al, 2006 ; Giraud et al, 2008 ; Smith et al, 2009 ).…”
Section: Introductionmentioning
confidence: 69%
“…The similarity of the root growth phenotype between aox1a and ucp1 seedlings in response to DTT ( Figure 3 ) provides correlative evidence for a degree of physiological redundancy between AOX1a and UCP1, even though their biochemical mechanisms are not related, and their regulation differs. Both AOX and UCP proteins can enhance the capacity of mitochondrial respiration to maintain cellular redox homeostasis and avoid metabolic over-reduction ( Barreto et al, 2020 ; Vanlerberghe et al, 2020 ; Alber and Vanlerberghe, 2021 ). Indications for in planta uncoupling function of UCP1 have been provided by impaired photorespiration in an Arabidopsis ucp1 mutant and enhanced drought and salt stress tolerance in Nicotiana tabacum UCP1 over-expressors ( Sweetlove et al, 2006 ; Begcy et al, 2011 ; Barreto et al, 2014 , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both modeling and experimental studies suggest that the mETC is a net sink for electrons derived from chloroplast metabolism in the light ( Krömer, 1995 ; Buckley and Adams, 2011 ; Cheung et al, 2015 ; Shameer et al, 2019 ; Yamada et al, 2020 ; Alber and Vanlerberghe, 2021 ). One abundant source of electrons is a carbon reaction in the photorespiration pathway.…”
Section: Distinct Pathways Of Mitochondrial Electron Transport To Oxygenmentioning
confidence: 99%
“…Another interesting observation was that UCP1 overexpression in tobacco resulted in an increased abundance of transcripts encoding several major cETC components, but not mETC components ( Laitz et al, 2015 ). In another study, inhibition of mitochondrial oxidative phosphorylation in the light with oligomycin resulted in a strong induction of both UCP and cATP synthase that was then able to maintain cETC activity and cell viability ( Alber and Vanlerberghe, 2021 ). These studies suggest a connection between mitochondrial UCP’s and photosynthesis that deserves further study.…”
Section: Distinct Pathways Of Mitochondrial Electron Transport To Oxygenmentioning
confidence: 99%
“…The benefit of increased AOX capacity towards photosynthesis therefore coincides with this period of rapid Pro metabolism. In actively photosynthesizing cells, AOX is thought to optimize photosynthetic rates by better allowing the mETC to safely oxidize excess reductant exported by the plastid (Dahal et al, 2015, Del-Saz et al, 2018, Alber and Vanlerberghe, 2021. Vishwakarma et al (2014) first observed higher NADH/NAD + and NADPH/NADP + ratios in high light treated aox1a Arabidopsis plants.…”
Section: Aox1a and Aox1d Aid In Post-salinity Recoverymentioning
confidence: 99%